Cakrawala“Cegah Kolesterol Dengan Waspada Konsumsi Lemak” - Paramitha Wirdani Ningsih Marlina; Agnes Maharani Puji Wulandari (STMIK Royal, 2023)
Abstract: Based on the results of National Basic Health Research in 2018 according to the proportion of total cholesterol levels in the population aged ≥45 years, 5 stated that as many as ≥10.5% of people had high cholesterol levels. The factors that cause hypercholesterolemia are nutritional status, especially obesity. Obesity is associated with lipoprotein, decreased High-Density Lipoprotein (HDL), and increased triglycerides and LDL, especially in central obesity. People who have a high percentage of body fat tend to have higher total cholesterol, LDL, and triglycerides compared to people who have normal weight. Nutrition counseling activities are carried out at the Johar Baru District Health Center which will be held on November 7, 2022. Respondents will be given a pre-test form containing 10 true and false statements for 10-15 minutes and then counseling will be carried out through poster media. After that, the respondent was given a post-test form. After 3 days of giving the material, monitoring, and evaluation were carried out on 5 respondents. This Monitoring and Evaluation will be carried out via telephone or the Whatsapp app. Based on the results of bivariate analysis, the results of knowledge obtained were p-value = 0.055 (p-value <0.05) so that it could be concluded that there was no difference in knowledge before and after nutritional education counseling using poster media in PTM patients at the Johar Baru District Health Center, Central Jakarta. Keywords: cholesterol; fat consumptionAbstrak: Berdasarkan Hasil Riset Kesehatan Dasar Nasional pada tahun 2018 menurut proporsi kadar kolesterol total pada penduduk umur ≥45 tahun, 5 menyebutkan bahwa sebanyak ≥10,5% masyarakat memiliki kadar kolesterol tinggi. Adapun faktor penyebab hiperkolesterolemia adalah status gizi terutama obesitas. Terdapat keterkaitan antara obesitas dengan lipoprotein, peningkatan trigliserida dan LDL, penurunan High Density Lipoprotein (HDL), terutama pada obesitas sentral. Individu dengan persen lemak tubuh yang tinggi cenderung memiliki total kolesterol, LDL dan trigliserida yang lebih tinggi dibandingkan dengan individu dengan berat badan normal. Kegiatan penyuluhan gizi dilakukan di Puskesmas Kecamatan johar Baru yang dilaksanakan pada tanggal 7 November 2022. Responden akan diberikan form pre test yang berisikan 10 pernyataan benar dan salah selama 10-15 menit dan selanjutnya akan dilakukan penyuluhan melalui media poster. Setelah itu responden diberikan form post test. Setelah 3 hari pemberian materi dilakukan monitoring dan evaluasi kepada 5 responden. Monitoring dan Evaluasi ini akan dilakukan melalui telepon ataupun app Whatsapp. Berdasarkan hasil analisis bivariat, didapatkan hasil pengetahuan nilai p value = 0.055 (p-value < 0,05) sehingga dapat disimpulkan bahwa tidak terdapat perbedaan pengetahuan sebelum dan sesudah penyuluhan edukasi gizi menggunakan media poster pada pasien PTM di Puskesmas Kecamatan Johar Baru Jakarta Pusat. Kata kunci: kolesterol; konsumsi lemak